Hold me - Mallery, Susan (Don Mills, Ontario : HQN, 2015)
Destiny Mills has a temporary assignment with the Fool's Gold search and rescue team. That means she is working with former skier Kipling Gilmore. He would like a fling with her, yet beneath Destinys cool facade is a woman who needs more than he's ever given.
Keywords: Skis and skiing -- Fiction; Man-woman relationships -- Fiction; Search and rescue operations -- Fiction; Love stories